Radiation Weakens Idealized Midlatitude Cyclones - Sophia A. K. Schäfer; Aiko Voigt (Geophysical Research Letters)
Abstract Midlatitude cyclones are strongly affected by diabatic processes. While the importance of latent heating is well established, the role of radiation has received little attention. Here we address this question for idealized cyclones by performing baroclinic life cycle simulations in the global atmosphere model ICON with and without radiation, and with transparent clouds. Radiation substantially weakens the simulated cyclone: peak eddy kinetic energy reduces by 50%, and minimum storm central pressure increases by 17 hPa. An analysis of the Lorenz energy cycle shows that the radiative weakening is not due to changes in the large‐scale environment alone but involves radiative processes within the cyclone. In fact, radiation warms the lower tropospheric part of the cyclone's warm conveyor belt and cools the upper tropospheric part. We hypothesize that radiation weakens the cyclone by destroying midtropospheric potential vorticity in the warm conveyor belt.